Implementasi Manajemen Berbasis Sekolah (MBS) dalam Kepemimpinan Kepala Sekolah - Fauzia Salmi; Ernawati Ernawati; Jonni Mardizal (Departement of Mathematics Education, 2024)
School-Based Management (SBM) is an approach that provides autonomy to Vocational High Schools (SMK) to manage resources independently and accountably. This article aims to examine the implementation of SBM in the leadership of SMK principals, focusing on supporting factors, challenges, and success strategies. The method used is a literature review, namely analyzing various studies and related literature. The results show that the success of SBM in SMK is influenced by the leadership competence of the principal, stakeholder participation, and support for educational policies. Principals with a transformational leadership style have been shown to be more effective in managing teams, encouraging innovation, and creating a collaborative culture in the SMK environment. However, challenges such as lack of training, limited funds, and resistance to change are still major obstacles. To overcome these challenges, it is necessary to strengthen regulations, continuous training, and increase the involvement of the community and the business world and industry (DUDI) in the decision-making process. This article provides important insights for the development of SBM-based education policies and practices in SMK to support improving the quality of graduates who are ready to work, continue their studies, or become entrepreneurs.